Marchiafava–Bignami Disease Associated with Spinal Involvement - Jhon Perea; María Belén Luis; Luciana Grimanesa Lázaro; Sergio Scollo; Agustina Tamargo; José Crespo; Maira Avalle; Horacio Solarz; Nora Fernández Liguori; Ricardo Alonso (Case Reports in Neurological Medicine)
Marchiafava–Bignami disease (MBD) is a rare disorder of unknown etiology, strongly associated with alcoholism and malnutrition. MBD causes primary involvement of the corpus callosum, leading to confusion, dysarthria, seizures, and frequent death. We report the case of a 54-year-old male without a history of alcoholism or known malabsorption disease, who presented with altered consciousness and neurologic impairment. Complex B deficiency was addressed. Magnetic resonance imaging (MRI) showed typical corpus callosum lesions. The clinical features and radiologic images suggested spinal cord involvement. Brain histopathologic findings were consistent with MBD. Despite vitamin replacement therapy, he had a poor outcome.